Controlled Monofunctionalization of Molecular Spherical Nucleic Acids on a Buckminster Fullerene Core - Gulumkar Vijay; Äärelä Antti; Moisio Olli; Rahkila Jani; Tähtinen Ville; Leimu Laura; Korsoff Niko; Korhonen Heidi; Poijärvi-Virta Päivi; Mikkola Satu; Nesati Victor; Vuorimaa-Laukkanen Elina; et al. (AMER CHEMICAL SOC, 2022)
An azide-functionalized 12-armed Buckminster fullerene has been monosubstituted in organic media with a substoichiometric amount of cyclooctyne-modified oligonucleo-tides. Exposing the intermediate products then to the same reaction (i. e., strain-promoted alkyne-azide cycloaddition, SPAAC) with an excess of slightly different oligonucleotide constituents in an aqueous medium yields molecularly defined monofunctionalized spherical nucleic acids (SNAs). This procedure offers a controlled synthesis scheme in which one oligonucleotide arm can be functionalized with labels or other conjugate groups (1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid, DOTA, and Alexa-488 demonstrated), whereas the rest of the 11 arms can be left unmodified or modified by other conjugate groups in order to decorate the SNAs' outer sphere. Extra attention has been paid to the homogeneity and authenticity of the C60-azide scaffold used for the assembly of full-armed SNAs.